O eterno caso dos adjetivos temporais e aspetuais: um contributo para a sua caracterização semântica - Ferreira, Idalina (2022)
The aim of this paper is to analyze the semantic behavior of adjectives that have been designated as temporal and aspectual in the literature, regarding the readings they can display. For this purpose, sixteen of these adjectives were selected and fifty occurrences of each one were randomly chosen and investigated. Overall, we observed a significant variety of readings associated with all the adjectives under scrutiny, which to greater or lesser degrees can express temporal, aspectual, temporoaspectual values, and readings of qualificative and relational adjectives. This diversity of possible readings raises problems for proposals that intend to classify this group of adjectives in a static manner (i.e., without considering the context).